Evaluation of carotid intima‐media thickness and factors associated with cardiovascular disease in children and adolescents with chronic kidney disease - Renata Lopes; Mauro Batista de Morais; Fernanda Luisa Ceragioli Oliveira; Ana Paula Brecheret; Ana Lucia Cardoso Santos Abreu; Maria Cristina de Andrade (Brazilian Society of Pediatrics, 2019)
Objective: To assess the carotid intima‐media thickness and factors associated with cardiovascular disease in children and adolescents with chronic kidney disease. Material and methods: Observational, cross‐sectional study carried out at the Universidade Federal de São Paulo (chronic kidney disease outpatient clinics) with 55 patients (60% males) with a median age of 11.9 years (I25-I75: 9.2-14.8 years). Of the 55 patients, 43 were on conservative treatment and 12 were on dialysis. Serum laboratory parameters (creatinine, uric acid, C‐reactive protein, total cholesterol and fractions, and triglycerides), nutritional status (z‐score of body mass index, z‐score of height/age), body fat (fat percentage and waist circumference), and blood pressure levels were evaluated. The carotid intima‐media thickness measure was evaluated by a single ultrasonographer and compared with percentiles established according to gender and height. Data collection was performed between May 2015 and March 2016. Results: Of the children and adolescents with chronic kidney disease, 74.5% (95% CI: 61.0; 85.3) showed an increase (>P95) in carotid intima‐media thickness. In patients with stages I and II hypertension, 90.9% had increased carotid intima‐media thickness. Nutritional status, body fat and laboratory tests were not associated with increased carotid intima‐media thickness. After multivariate adjustment, only puberty (PR = 1.30, p = 0.037) and stages I and II arterial hypertension (PR = 1.42, p = 0.011) were independently associated with carotid intima‐media thickness alterations. Conclusion: The prevalence of increased carotid thickness was high in children and adolescents with chronic kidney disease. Puberty and arterial hypertension were independently associated with increased carotid intima‐media thickness. Resumo: Objetivo: Avaliar a espessura médio‐intimal da carótida e os fatores associados à doença cardiovascular em crianças e adolescentes com doença renal crônica. Material e métodos: Estudo observacional transversal feito na Universidade Federal de São Paulo (ambulatórios de doença renal crônica) com 55 pacientes (60% do sexo masculino) com mediana de 11,9 anos (I25‐I75: 9,2-14,8). Dos 55 pacientes, 43 estavam em tratamento conservador e 12 em terapia dialítica. Foram avaliados os parâmetros laboratoriais séricos (creatinina, ácido úrico, proteína C‐reativa, colesterol total e frações e triglicérides), estado nutricional (escore z de índice de massa corpórea, escore z de estatura/idade), gordura corporal (percentual de gordura e circunferência abdominal) e pressão arterial. A medida da espessura médio‐intimal da carótida foi avaliada por um único ultrassonografista e comparada com percentis estabelecidos de acordo com o sexo e a estatura. A coleta de dados foi feita entre maio de 2015 e março de 2016. Resultados: Das crianças e adolescentes com doença renal crônica, 74,5% (IC 95%: 61,0; 85,3) apresentaram aumento (> P95) da espessura médio‐intimal da carótida. Nos pacientes com hipertensão arterial estágios I e II, 90,9% apresentaram aumento da espessura médio‐intimal da carótida. O estado nutricional, a gordura corporal e os exames laboratoriais não apresentaram associação com o aumento da espessura médio‐intimal da carótida. Após ajuste multivariado, apenas a puberdade (RP = 1,30; p = 0,037) e a hipertensão arterial estágios I e II (RP = 1,42; p = 0,011) mostraram‐se independentemente associados à alteração da espessura médio‐intimal da carótida. Conclusão: A prevalência do aumento da espessura da carótida foi elevada em crianças e adolescentes com doença renal crônica. A puberdade e a hipertensão arterial mostraram‐se independentemente associadas ao aumento da espessura médio‐intimal da carótida. Keywords: Chronic kidney disease, Cardiovascular diseases, Carotid intima‐media thickness, Adolescents, Children, Palavras‐chave: Insuficiência renal crônica, Doenças cardiovasculares, Espessura intima‐média carotídea, Adolescentes, Crianças